ANALISIS EFISIENSI BELANJA DAERAH URUSAN KESEHATAN DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA): STUDI PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI BANTEN - Yanti, Putri; Kustiani, Nur Aisyah (Polytechnic of State Finance STAN, 2016)
This study aims to measure the efficiency of local government spending of health affairs using Data Envelopment Analysis (DEA). DEA method can measure the efficiency of a government entity by using multi-input and multi-output. This is consistent with the character of the government that has the task of providing a wide range of public services to solve complex problems in the society. The efficiency measure generated by the DEA is relative measure, comparing with benchmarks decision making unit (DMU) that have the highest efficiency among the other DMUs in the sample, so the results would be different if the sample is changed. Therefore, in the election of DMU should be based on some similar characteristics. DEA results can be used to identify which input or output must be increased if a DMU needs to increase its efficiency. The results from this study indicate that Tangerang and Cilegon has the highest efficiency and Tangerang district (kabupaten Tangerang) should increase the number of intermediate output and its end output to improve the efficiency of health spending. The DEA method can be used by the government to create a climate of efficient budgets in a field of government service